Comportamiento del crecimiento en diámetro y altura total en las plantas de Swietenia macrophylla King “caoba” con diferentes dosis y frecuencia de fumigación del fertilizante foliar en plantación, Puerto Almendra, Loreto, Perú – 2022 - Arevalo Zevallos, Jossie Stephanie (2023)
The thesis was developed at CIEFOR Puerto Almendra - FCF - UNAP, Loreto, Peru; whose objective was to define the growth of the diameter and total height of the Swietenia macrophylla King "caoba" plants treated with different doses and frequencies of foliar fertilization in plantation. Three doses of foliar fertilization were considered: 20 ml of concentrate / 200 ml of water; 40 ml of concentrate / 20000ml water; 60 ml of concentrate / 20000 ml of water and the frequency of fumigation was 2 times a week, with 3 repetitions; the diameter and the total height were evaluated; the design was simple at random whose results are presented below: the best increase in total height and diameter was identified in Dose 3 with 109.2 cm and 14.2 mm. However, in both cases there is no statistical difference between the treatments (foliar fertilization dose).